Klasifikasi Kematangan Citra Buah Tomat Berdasarkan Ekstraksi Fitur Warna Menggunakan Metode K-NN - Ahmad Badri Maulana Widat; Achmad Baijuri; Farihin Lazim (G-Tech: Jurnal Teknologi Terapan, 2024)
Tomatoes are a vegetable commodity that has high economic value and is widely consumed by the public. Tomato ripeness plays an important role in determining the quality and durability of tomato products. The process of ripening tomatoes only takes a short time. To overcome this problem, researchers used the K-NN method to classify tomato fruit ripeness based on color feature extraction. In the process of classifying the maturity level of tomatoes, 150 datasets from 3 different maturity classes are used, namely 50 ripe, 50 ripe and 50 unripe. The 150 datasets were divided into 90 training data and 60 test data. The classification results using K-NN show the optimal value, namely k=5 with an accuracy of 98.33%.